Mapping of retinal and geniculate neurons onto striate cortex of macaque - Schein, SJ (J Neurosci, 1987)
A unity ratio between geniculate and ganglion cells can be shown in the macaque visual system. Comparison of the densities (cells/deg2) in the dorsal lateral geniculate nucleus (dLGN) of parvocellular (P) and magnocellular (M) cells, respectively, representing color-opponent and broad-band ganglion cells, with cortical magnification (mm2/deg2) gives the number of afferents per square millimeter in striate cortex (V1). For P cells, this afferent density rises only slightly with eccentricity, indicating that V1 magnification is approximately proportional to the density of P cells. The density of cytochrome oxidase puffs in V1 also rises only slightly with eccentricity. As a result, the number of P-cell afferents per puff-centered module is remarkably constant throughout V1. Our findings thus support a novel hypothesis of peripheral scaling, in which V1 cortical magnification is based on the mapping of just 1 class of afferent onto V1 modules. This “P-cell module” in V1 may be composed of submodules corresponding anatomically to the honeycomb cell in layer 4A of V1 and physiologically to a minimal complete set of color-opponent ganglion cells. In contrast, the afferent density of M cells rises steeply with eccentricity, so that the reciprocal of their afferent density, the cortical “domain” of M cells, declines with eccentricity. This decline is similar to that of point-image area in V1. As a result, the number of M cells per point-image area is nearly constant. This quantity is analogous to the receptive-field coverage factor in the retina, which for M cells is fairly constant and greater than unity at all eccentricities. The results show fundamental differences between the neural maps of these 2 major cell types, differences that are likely to have psychophysical consequences.